Pengaruh Influencer Dan Brand Ambassador Terhadap Keputusan Pembelian Generasi Z Pada Marketplace Di Surabaya - Aldira Layza Madina; Dhyah Wulansari (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to determine the influence of influencers and brand ambassadors on generation Z purchasing decisions on marketplaces in Surabaya. Data analysis was carried out using SPSS version 25 software. Validity and reliability tests were carried out first to ensure the research instrument met the required criteria. Next, regression analysis is used to test the simultaneous influence of the independent variables (Influencer and Brand Ambassador) on the dependent variable (Purchase Decision). Using SPSS 25 software with a sample size of 32 respondents. The population in this study were employees of PT. Greentech Asia Sejahtera by sampling using Saturated Samples. The results of this research are influencers and brand ambassadors on generation Z purchasing decisions on the marketplace in Surabaya. The Influencer (X1) and Brand Ambassador (X2) variables simultaneously influence the Purchasing Decision variable (Y), the magnitude of the influence is 30% and the remaining 70% is caused by other variables.